Proceedings of the Ninth ACM SIGKDD International Conference on Knowledge Discovery and Data Mining 2003
DOI: 10.1145/956750.956847
|View full text |Cite
|
Sign up to set email alerts
|

Towards NIC-based intrusion detection

Abstract: We present and evaluate a NIC-based network intrusion detection system. Intrusion detection at the NIC makes the system potentially tamper-proof and is naturally extensible to work in a distributed setting. Simple anomaly detection and signature detection based models have been implemented on the NIC firmware, which has its own processor and memory. We empirically evaluate such systems from the perspective of quality and performance (bandwidth of acceptable messages) under varying conditions of host load. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…To ensure that rules correspond to strong patterns the rules with low support values are pruned. An application of this technique for intrusion detection was used in ADAM system [30,31] and in [33] for intrusion detection embedded on the network interface card. LERAD method [34] generates association rules from data in the form P(notW|U), which is conditional probability of one subset of attributes taking on a particular set of values (denoted by notW) given that a disjoint subset of attributes takes on a particular set of values (denoted by U).…”
Section: Rule-based Methodsmentioning
confidence: 99%
“…To ensure that rules correspond to strong patterns the rules with low support values are pruned. An application of this technique for intrusion detection was used in ADAM system [30,31] and in [33] for intrusion detection embedded on the network interface card. LERAD method [34] generates association rules from data in the form P(notW|U), which is conditional probability of one subset of attributes taking on a particular set of values (denoted by notW) given that a disjoint subset of attributes takes on a particular set of values (denoted by U).…”
Section: Rule-based Methodsmentioning
confidence: 99%
“…3) Clustering-based: These methods detect anomalies after clustering the samples. The samples not belonging to any cluster, the samples far from the cluster centers, and the samples in very sparse or small clusters [36,38] are treated as isolated anomalies, edge anomalies, and sparsely clustered anomalies, respectively. Yu et al [37] applied a wavelet transformation to the quantized feature space and found sample clusters in this space.…”
Section: ) Statistical Model-basedmentioning
confidence: 99%
“…Such approaches do not work well in even moderately high-dimensional (multivariate) spaces, and finding the right model is often a difficult task in its own right. Simplified probabilistic models suffer from a high false positive rate (Mahoney and Chan, 2002;Otey et al, 2003). Also, methods based on computational geometry (Johnson et al, 1998) do not scale well as the number of dimensions increase.…”
Section: Related Workmentioning
confidence: 99%